A healthy amount of privacy: quantifying privacy concerns in medicine - Cofone, IC (Cleveland-Marshall College of Law, 2017)
With recent developments in e-health, concerns have been raised regarding the privacy of patients who are monitored with such treatments. I propose a simple method to incorporate these concerns into a standard health impact evaluation, based on quality-adjusted life years and the incremental cost-effectiveness ratio. This method provides a way to objectively value privacy concerns and balance them with health benefits. Hence, it can guide doctors and policymakers into incorporating privacy considerations and making better choices regarding e-health programs. This method can also be tested on existing economic evaluations to compare outcomes and gauge the extent to which privacy issues in medical treatments should be taken seriously.